Legalitas Perppu Cipta Kerja Diantara Undang-Undang Cipta Kerja Dan Putusan Mahkamah Konstitusi - Jazil, Syokron; Syakdiyah, Halimatus (Fakultas Hukum Universitas Islam Malang, 2024)
The issuance of the Job Creation Perppu has raised many pros and cons from various figures. The research wants to find out how big the pros and cons are over the enactment of the Job Creation Perppu and the conformity between actual phenomena and ideal phenomena. This research uses a normative juridical research method based on a statutory, case, and conceptual approaches. The results show that the Perppu on Job Creation is a product of a failure to understand the Constitutional Court's Decision Number 91/PUU-XVIII/2020, so that its legality and existence are crucial problems. This is also related to the legal considerations of 4 important points in the issuance of the Perppu which contradict facts and theories.